2006
DOI: 10.1016/j.childyouth.2005.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Review of a community-based youth counselling service in Ireland

Abstract: The structure and operation of a community-based youth counselling service operated by the Kildare Youth Services (KYS), Ireland, are examined with a view to highlighting the preventative nature of such a service. Presenting problems are explored, in the context of the wider social milieu. Particularly, recent trends in sexual behaviour, substance abuse and child sexual abuse are examined. Interviews were conducted with a sample of professionals who referred clients, patients and students to the KYS Youth Coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Three qualitative evaluations reported on the acceptability of counselling within specialist school settings (Cobbett, 2016; Pattison & Harris, 2006; Warr, 2010). Three evaluations reported on the acceptability of counselling within community settings (Duncan et al, 2020; Lalor et al, 2006; Wilkinson et al, 2018). However, there were some learners who reported issues around counselling acceptability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three qualitative evaluations reported on the acceptability of counselling within specialist school settings (Cobbett, 2016; Pattison & Harris, 2006; Warr, 2010). Three evaluations reported on the acceptability of counselling within community settings (Duncan et al, 2020; Lalor et al, 2006; Wilkinson et al, 2018). However, there were some learners who reported issues around counselling acceptability.…”
Section: Resultsmentioning
confidence: 99%
“…There were several implementation issues identified that could have affected the overall effectiveness outcomes. Many of the participants did not know about the service or had misconceptions about the service, which inhibited access (Duffy et al, 2021;Fox & Butler, 2007;Government W, 2011aGovernment W, , 2011bHamilton-Roberts, 2012;Hennigan & Goss, 2016;Lalor et al, 2006;Le Surf & Lynch, 1999;McArthur et al, 2016;Parsons & Dubrow-Marshall, 2018;Pattison, 2010;Prior, 2012aPrior, , 2012bSpratt et al, 2007). In addition, there were issues with the counselling space and its location leading to concerns about confidentiality (Duffy et al, 2021;Fox & Butler, 2007;Le Surf & Lynch, 1999;Parsons & Dubrow-Marshall, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, adolescents can meet the counselor in a variety of circumstances and he/she can work to reduce barriers by means of multiple ways. The integration in the school setting allows "infiltration" to parts of the community that other counselors would have little access to (Lalor, O'Dwyer, & McCrann, 2006).…”
Section: Limitations Implications For Social Work and Conclusionmentioning
confidence: 99%